2009
DOI: 10.1261/rna.1795410
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)-binding protein modulates mRNA susceptibility to cap-dependent miRNA-mediated repression

Abstract: MicroRNAs (miRNAs) regulate gene expression post-transcriptionally through binding specific sites within the 39 untranslated regions (UTRs) of their target mRNAs. Numerous investigations have documented repressive effects of miRNAs and identified factors required for their activity. However, the precise mechanisms by which miRNAs modulate gene expression are still obscure. Here, we have examined the effects of multiple miRNAs on diverse target transcripts containing artificial or naturally occurring 39 UTRs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 59 publications
7
56
0
1
Order By: Relevance
“…However, we have not been able to rule out the involvement of rapid mRNA degradation in the observed silencing effect. These observations fi t well with previous fi ndings demonstrating the importance of m 7 G-cap recognition in mRNA processing and regulation, such as the work by Walters et al (47) who demonstrated the presence of a cap structure to be suffi cient to allow miRNA-mediated silencing to occur.…”
Section: Pre-initiation Silencingsupporting
confidence: 90%
See 1 more Smart Citation
“…However, we have not been able to rule out the involvement of rapid mRNA degradation in the observed silencing effect. These observations fi t well with previous fi ndings demonstrating the importance of m 7 G-cap recognition in mRNA processing and regulation, such as the work by Walters et al (47) who demonstrated the presence of a cap structure to be suffi cient to allow miRNA-mediated silencing to occur.…”
Section: Pre-initiation Silencingsupporting
confidence: 90%
“…However, as previously highlighted, a degree of controversy exists in the literature over the interpretation of such results between contrasting studies; these are reviewed in Table 1 . Recent fi ndings by Walters et al (47) may allude to a more defi nitive explanation.…”
Section: Recognition Of M 7 G-capmentioning
confidence: 96%
“…The extent of miRNA-mediated repression has been shown to be dependent on levels of the protein. 110,135 Paip2 is a negative regulator of PABP function, and acts by competing with eIF4G for interaction with PABP. 136,137 In accordance with the effects of PABP overexpression, increased levels of Paip2 were shown to enhance miRNA-mediated repression.…”
Section: Regulation Of Mirisc and Its Functional Diversitymentioning
confidence: 99%
“…136,137 In accordance with the effects of PABP overexpression, increased levels of Paip2 were shown to enhance miRNA-mediated repression. 110 PABP also undergoes a number of posttranslational modifications, 138,139 which may in the future be shown to influence its effects in the miRNA repression pathway.…”
Section: Regulation Of Mirisc and Its Functional Diversitymentioning
confidence: 99%
See 1 more Smart Citation